Existence and Uniqueness Results for Perturbed Neumann Boundary Value Problems. (29th July 2010) - Zhang, Jieming; Zhai, Chengbo
Abstract : Using a fixed point theorem of generalα -concave operators, we present in this paper criteria which guarantee the existence and uniqueness of positive solutions for two classes of nonlinear perturbed Neumann boundary value problems for second-order differential equations. The theorems for Neumann boundary value problems obtained are very general.